Quantifying regional consumption-based health impacts attributable to ambient air pollution in China. (March 2018) - Zhang, Yanxia; Qu, Shen; Zhao, Jing; Zhu, Ge; Zhang, Yanxu; Lu, Xi; Sabel, Clive E.; Wang, Haikun
Abstract: Serious air pollution has caused about one million premature deaths per year in China recently. Besides cross-border atmospheric transport of air pollution, trade also relocates pollution and related health impacts across China as a result of the spatial separation between consumption and production. This study proposes an approach for calculating the health impacts of emissions due to a region's consumption based on a multidisciplinary methodology coupling economic, atmospheric, and epidemiological models. These analyses were performed for China's Beijing and Hebei provinces. It was found that these provinces' consumption-based premature deaths attributable to ambient PM2.5 were respectively 22, 500 and 49, 700, which were 23% higher and 37% lower than the numbers solely within their boundaries in 2007. The difference between the effects of trade and trade-related emissions on premature deaths attributable to air pollution in a region has also been clarified. The results illustrate the large and broad impact of domestic trade on regional air quality and the need for comprehensive consideration of supply chains in designing policy to mitigate the negative health impacts of air pollution across China. Highlights: An approach for calculating consumption-based health impacts was proposed. Consumption-based health impacts of Beijing and Hebei province were quantified. Domestic trading was found to greatly influence regional air quality in China. Effects of trade and trade-related emissions on health impacts were distinguished.